D-DIMER AND FIBRINOGEN IN PATIENTS UNDERWENT SURGERY IN MALIGNANT AND BENIGN OVARIAN TUMOR - Ismail Aswin; Herman Hariman; Fauzie Sahil (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Ovarian tumour ranks second in gynecology tumour cases and ranks second in gynecology tumour death in Indonesia. Tumour cause hypercoagulable that increase risk of thrombosis by procoagulant mechanism. Tumout cells also can cause hyperfibrinogenemmia that can cause bleeding. The aim of study was to know D-dimer and fibrinogen value to investigate primary hyperfibrinolysis on malignant and benign ovarian tumour; and to know whether operation procedure on malignant and benign tumour change D-dimer and fibrinogen value. Prospective analysis study, subject were malignant and benign ovarian tumour patients undergoing surgery in Haji Adam Malik Hospital, Medan. One way Annova test dan Wilcoxon Sum-Rank test were performed. Stastical differentiation is indicate with p<0,05. Study subject was 16 patient where 8 malignant and benign ovarian tumour patient respectively. Malignant ovarian tumour D-dimer values was higher than benign ovarian tumour (p<0,01) that indicate fibrinolysis increase in malignant ovarian tumour. Malignant ovarian tumour fibrinogen values as same as benign ovarian tumour (p>0,05) that indicate the fibrinolysis in ovarian tumour wasn't primary hyperfibrinolysis. Surgery procedure didn't influence D-dimer and fibrinogen values. Primary hyperfibrinolysis wasn't occur in ovarian tumour.Keywords : Ovarian tumour, malignant, benign, D-dimer, fibrinogen.